Distribution of HLA-B Alleles and Haplotypes in Qatari: Recommendation for Establishing Pharmacogenomic Markers Screening for Drug Hypersensitivity - Dashti, Mohammed; Al-Matrouk, Abdullah; Channanath, Arshad; Hebbar, Prashantha; Al-Mulla, Fahd; Thanaraj, Thangavel Alphonse (Frontiers in Pharmacology, 2022)
Human leukocyte antigen (HLA) proteins are present at the cellular surface of antigen-presenting cells and play a crucial role in the adaptive immune response. Class I genes, specifically certain HLA-B alleles, are associated with adverse drug reactions (ADRs) and are used as pharmacogenetic markers. Although ADRs are a common causes of hospitalization and mortality, the data on the prevalence of HLA-B pharmacogenetics markers in Arab countries are scarce. In this study, we investigated the frequencies of major HLA-B pharmacogenomics markers in the Qatari population. Next-generation sequencing data from 1,098 Qatari individuals were employed for HLA-B typing using HLA-HD version 1.4.0 and IPD-IMGT/HLA database. In addition, HLA-B pharmacogenetics markers were obtained from the HLA Adverse Drug Reaction Database. In total, 469 major HLA-B pharmacogenetic markers were identified, with HLA-B*51:01 being the most frequent pharmacogenetic marker (26.67%) in the Qatari population. Moreover, HLA-B*51:01 is associated with phenytoin- and clindamycin-induced ADRs. The second most frequent pharmacogenetic marker was the HLA-B*58:01 allele (6.56%), which is associated with allopurinol-induced ADRs. The third most frequent pharmacogenetic marker was the HLA-B*44:03 allele, which is associated with phenytoin-induced ADRs. The establishment of a pharmacogenetics screening program in Qatar for cost effective interventions aimed at preventing drug-induced hypersensitivity can be aided by the highly prevalent HLA-B pharmacogenetic markers detected here.